A LIBERDADE ACADÊMICA ENQUANTO GARANTIA INSTITUCIONAL: UMA ANÁLISE A PARTIR DE SWEEZY VS. NEW HAMPSHIRE, 354 U.S. 234 (1957) - Travincas, Amanda Costa Thomé; Lima, Manuela Ithamar (Revista da AJURIS - Qualis A2, 2016)
ACADEMIC FREEDOM AS AN INSTITUTIONAL GUARANTEE: AN ANALYSIS FROM SWEEZY VS. NEW HAMPSHIRE, 354 U.S. 234(1957) RESUMO: Este estudo propõe-se a analisar a interpretação atribuída pela Suprema Corte norte-americana à liberdade acadêmica enquanto garantia institucional. É contumaz a alusão a Sweezy vs. New Hampshire como o precedente que inaugura a narrativa acerca da liberdade acadêmica na Corte e, pontualmente, que cuida de acentuar a faceta da qual decorre a competência das instituições de ensino para dar tonalidade às atividades desempenhadas pelos atores envolvidos no contexto educacional. A abordagem ocupa-se do caso para a propulsão da discussão referente ao sentido e ao alcance da atribuição de autonomia às universidades, a fim de, mediante abordagem indutiva, atentar para as consequências de tal reconhecimento no tocante à atuação docente. PALAVRAS-CHAVE: liberdade de expressão; liberdade acadêmica; garantia institucional; sweezy vs. new hampshire. ABSTRACT: This study aims to examine the interpretation given by the US Supreme Court to academic freedom as an institutional guarantee. It is contumacious the allusion to Sweezy vs. New Hampshire as the precedent that opens the narrative about academic freedom in the Court and, exactly, that takes care to emphasize the aspect which follows the competence of educational institutions to give emphasis to the activities performed by the actors involved in the educational context. The approach is concerned with the case to propel the discussion regarding the meaning and scope of granting autonomy to Universities, in order to, by induction, pay attention to the consequences of such recognition in relation specifically to teaching practice. KEYWORDS: freedom of speech; academic freedom; institutional guarantee; sweezy vs. new hampshire. SUMÁRIO: Notas introdutórias; 1 No descomeço, a liberdade de expressão; 2 Sweezy e a narrativa da liberdade acadêmica na Suprema Corte norte-americana; 3 A liberdade acadêmica enquanto garantia institucional; Considerações finais; Referências. SUMMARY: Introductory notes; 1 Before the beginnig, the freedom of expression; 2 Sweezy and the narrative of academic freedom in the US Supreme Court; 3 Academic freedom as an institutional guarantee; Final considerations; References.